2017
DOI: 10.18203/2320-1770.ijrcog20171440
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between number of mature eggs retrieved and live birth rate in IVF treatment

Abstract: INTRODUCTIONThe development of assisted reproductive technologies has revolutionized the treatment of Infertility. The 1 st IVF baby Louise Brown was born in 1978 by the pioneering efforts of Prof Edwards and Steptoe for which Prof Edwards was honoured with the Nobel Prize in medicine in 2010. The first IVF was natural cycle IVF in which one oocyte during natural cycle was retrieved. In natural cycle of a female one mature oocyte is released so that the rate of cancellation of cycle was high and success was le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
0
0
Order By: Relevance
“…Our finding was in agreement with a study done by Rana et al who also showed an increase in live birth rates with an increasing number of mature eggs. 25 Data relating pregnancy rate and number of number of embryos obtained also showed a significant relation (p = 0.002).…”
Section: Discussionmentioning
confidence: 87%
“…Our finding was in agreement with a study done by Rana et al who also showed an increase in live birth rates with an increasing number of mature eggs. 25 Data relating pregnancy rate and number of number of embryos obtained also showed a significant relation (p = 0.002).…”
Section: Discussionmentioning
confidence: 87%